Analisis User Requirement Terhadap Aplikasi Online Video Conference - Abdi Nata Kusuma; Ariftiarno, Reza; Widyarto, Setyawan (Proceedings of the Informatics Conference, 2026)
The COVID-19 pandemic accelerated the adoption of online communication technologies, particularly video conferencing platforms, to support remote work, education, and collaboration. Despite the widespread use of applications such as Zoom and Google Meet, users still experience limitations related to functionality and user experience. This study aims to analyze user requirements for the development of an improved online video conferencing application. A survey-based approach was employed to gather user perspectives on existing platforms. An online questionnaire consisting of 15 questions was distributed to purposively selected respondents. Eight participants aged between 13 and over 50 years completed the survey, providing insights into their experiences, preferences, and expectations regarding video conferencing tools. The findings indicate that users prioritize features such as shared collaborative boards, improved meeting room management, and more immersive interaction capabilities. Respondents also prefer web-based platforms due to their accessibility across devices. These findings highlight the importance of incorporating user-centered design principles in developing more effective and user-friendly video conferencing systems.